COMPARATIVE ANALYSIS OF DISEASES CAUSED BY CONDITIONAL PATHOGENIC MICROORGANISMS (CPM). (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
General symptoms of gastroenterocolitic form of salmonellosis and  observed when CPM is called. Children's age, household contact infection, symptoms of poisoning, damage to the gastrointestinal tract. Diseases caused by conditionally pathogenic microorganisms and their analysis are presented in this article.